Nuclear genome size: are we getting closer? - Dolezel, Jaroslav; Greilhuber, Johann (Cytometry. Part A, 2010)
Correct information on genome size is important in many areas of research. For a long time, scientists have been struggling to understand the reason for the huge variation in eukaryotic genome size and its biological significance. More recently, the knowledge on genome size has become important to structure genome sequencing projects as their scale and cost depend on genome size. Despite the fact that the first estimates of genome size in eukaryotes were made more than 50 years ago, we are still not quite sure about the exact genome size in practically all animal and plant species. Moreover, different estimates continue to be published for the same species. These discrepancies compromise data comparison and interpretation and point to methodological problems, which include standardization. This article assesses the current state of DNA reference standards for flow cytometry and the issues related to their calibration.
Keywords: DNA; DNA rostlinná; Eukaryota; Reference Standards; DNA, Plant; genom; Genome; průtoková cytometrie; Animals; lidé; buněčné jádro; Cell Nucleus; Humans; zvířata; referenční standardy; Flow Cytometry